Initial care of patients with head trauma and acute cranial hypertension - Cam Páucar, Juan Luís (2011)
Traumatic brain injury (TBI) is a common cause of morbidity and mortality in our cities, and the high incidence of traffic accidents raise the frequency of occurrence of this condition. It is important to take into account the initial treatment for stabilizing patients, including airway management, hemodynamic stabilization, initial treatment of intracranial hypertension (ICH), sedation and analgesia, anticonvulsant use, and prophylaxis of venous thromboembolic events, avoiding secondary complications and improving the prognosis of this condition.